On the identity of Pronotonyx laevis (Miers, 1884) (Crustacea: Brachyura: Pilumnidae) - Ahyong, Shane T.; Ng, Peter K.l. (Zootaxa, 2023)
The poorly known brachyuran crab, Pronotonyx laevis Ward, 1936, from northern Australia, is redescribed based on type and other material. We document adults of both sexes and confirm the taxonomic placement of the Pronotonyx in the Pilumnidae. Pronotonyx is most similar to the Australian Pseudocryptocoeloma parvum Ward, 1936, differing in features of the carapace and pereopods.